Effects of Pilot Oil Injection Timing on Combustion, Covariance and Knocking of a Natural Gas–Diesel Duel-Fuel Low-Speed Engine - Wei Cunfeng; Chen Xiang-Xiang; Chen Liang; Li Pengfei; Liu Mingrui (Polish Maritime Research)
Dual-fuel engines, which are powered by natural gas while using a small amount of diesel for ignition, have become an attractive option in the marine sector due to their fuel flexibility and relatively good emission characteristics. Altering the fuel injection timing can change the combustion state of natural gas in the cylinder, which in turn affects engine stability and leads to engine knocking.